Psychometric Properties of the Coach-Created Empowering and Disempowering Motivational Climate Questionnaire (EDMCQ-C) in a Brazilian Sample of Athletes: An ESEM Approach - Angelo, Daniela Lopes (2023)
The objectives of this study were to assess the psychometric properties of the Coach-created Empowering and Disempowering Motivational Climate Questionnaire (EDMCQ-C) by testing four different hypotheses. A procedure of translation and adaptation of the instrument between different languages and cultures was carried out. A total of 350 national level Brazilian athletes (aged between 15 and 17 years; mean = 17.0, SD = 1.7) completed the questionnaire. Confirmatory Factor Analysis (CFA) and Exploratory Structural Equation Modelling (ESEM) were performed. Consistent with previous work on the EDMCQ-C, all solutions failed to achieve suitable levels of fit for a hierarchical model represented by five climate dimensions (autonomy-supportive, controlling, task-involving, ego-involving, and socially-supportive) and two global dimensions (empowering and disempowering). The 2-ESEM solution provided a satisfactory fit for the first-order model with two global factors supported. The 2-ESEM version of the questionnaire showed adequate predictive and discriminant validity, good internal consistency, and invariance across gender. Such results suggest that the EDMCQ-C is a promising scale to assess Brazilian athletes’ perception of the over-arching empowering and disempowering features of the coach-created motivational climate.